Rozum jako naturalna droga do wiary - zapomniana koncepcja Teodoreta z Cyru - Dobosz, Wojciech Piotr (Vox Patrum, 2019)
The article focuses on the Theodoret of Cyrrhus, a little known in the Polish Patrology Syrian Church’s Father, who in his book “Healing Hellenic Diseases” created an original apologetic method. It consisted in the presentation of reason – rational thinking as a natural way to faith, in order to convince the educated representatives of Greek culture to Christianity. Theodoret, who had classical Greek education and experience of strict monastic life in the Syrian form of asceticism was able to combine both of these realities to indicate Christianity as a true philosophy (fullness of knowledge) and the monk as the ideal of a philosopher. The main method of Theodoret was to evidence the rationality of Christianity by creating demands for the rationality of science. He made this by alluding to the thoughts and opinions of the authorities recognized in Greek culture. In modern time this method could become the way to convince all rational world to accept the Christian teaching and consequently to open to the fullness of the truth of being - Jesus Christ.